2014
DOI: 10.1042/bj20131242
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide synthase 4 deficiency in mice causes lipid alterations in sebum and results in alopecia

Abstract: Five ceramide synthases (CerS2-CerS6) are expressed in mouse skin. Although CerS3 has been shown to fulfill an essential function during skin development, neither CerS6- nor CerS2-deficient mice show an obvious skin phenotype. In order to study the role of CerS4, we generated CerS4-deficient mice (Cers4-/-) and CerS4-specific antibodies. With these biological tools we analysed the tissue distribution and determined the cell-type specific expression of CerS4 in suprabasal epidermal layers of footpads as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 54 publications
5
58
0
Order By: Relevance
“…CerS3- Significance was determined by Student's t test. *P < 0.05, **P < 0.01, ***P < 0.001. generated ultra-long sphingolipids play key roles in the homeostasis of skin barrier function (34), whereas deficiency of CerS4 is associated with skin disorders such as irreversible alopecia (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…CerS3- Significance was determined by Student's t test. *P < 0.05, **P < 0.01, ***P < 0.001. generated ultra-long sphingolipids play key roles in the homeostasis of skin barrier function (34), whereas deficiency of CerS4 is associated with skin disorders such as irreversible alopecia (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Here we briefly describe the (Laviad et al, 2008). Suborgan-and cell-specific CerS distribution is described according to protein expression (Ginkel et al, 2012;Jennemann et al, 2012;Ebel et al, 2013Ebel et al, , 2014Kremser et al, 2013) …”
Section: Introductionmentioning
confidence: 99%
“…CerS3 KO mice are lethal shortly after birth due to skin barrier disruption (2), and it was shown that CerS3 is also required for meiotic cytokinesis during spermatogenesis (15). CerS4-deficient mice show agerelated hair loss (6), due to altered stem cell maintenance (16), and CerS6-deficient mice show behavioral abnormalities, including hind limb clasping (12). The diverse phenotypes of CerS mice suggest that ceramides exhibit chain length-specific functions.…”
mentioning
confidence: 99%
“…However, the data on ceramidedependent inhibition of AKT are largely derived from cell culture studies where water-soluble synthetic C 2 -ceramide was added exogenously to the culture medium to examine the 49-228-73-62639; E-mail: m.hoch@uni-bonn.de. 6 The abbreviations used are: CerS, ceramide synthase; NBD, 7-nitro-2-1,3-benzoxadiazol-4-yl; oxa-1,3-diazol-4-yl)); TAG, triglyceride; S1P, sphingosine 1-phosphate; WAT, white adipose tissue; eWAT, epididymal WAT; ANOVA, analysis of variance; HFD, high fat diet; LFD, low fat diet; ACC, acetyl-CoA carboxylase; AMPK, AMP-activated protein kinase; AKT, protein kinase B/Akt. …”
mentioning
confidence: 99%
See 1 more Smart Citation